1996
DOI: 10.1007/bf00434546
|View full text |Cite
|
Sign up to set email alerts
|

Knee joint proprioception in normal volunteers and patients with anterior cruciate ligament tears, taking special account of the effect of a knee bandage

Abstract: Proprioception of the knee joint was tested in 30 healthy volunteers with clinically inconspicuous knee joints. To examine proprioception, an angle reproduction test was performed. We could not document any differences between the left and the right knee joint or between men and women. At the mid-range, proprioception was worse compared with the end range of motion. In addition, 25 patients with an isolated rupture of the anterior cruciate ligament were evaluated, 14 before and 11 after operative anterior cruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
89
2
3

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(100 citation statements)
references
References 16 publications
6
89
2
3
Order By: Relevance
“…This has also been reported by others (13,24). The magnitude of the mean difference between the groups was over 30%, which is in line with a previous study where the same device was used (24).…”
Section: Discussionsupporting
confidence: 90%
“…This has also been reported by others (13,24). The magnitude of the mean difference between the groups was over 30%, which is in line with a previous study where the same device was used (24).…”
Section: Discussionsupporting
confidence: 90%
“…The methods chosen in our study were passive angle reproduction (PAR) (Perlau et al, 1995) active angle reproduction (AAR) tests (Fridén et al, 1996). As the former studies have demonstrated there were no differences proprioceptive measures between dominant and non-dominant limbs, and so the right leg of each subject was selected to ease the testing setup (Jerosch & Prymka, 1996).…”
Section: Measurement Of Proprioceptionmentioning
confidence: 99%
“…The knee starting position was at 90° of knee flexion and the target angle was 45°, this angle is believed to be in the working range of the knee during daily weight-bearing activities (Jerosch & Prymka, 1996). In the first trial, the lever arm passively extended the test limb, to the target angle of 45° without resistance to the movement.…”
Section: Passive Angle Reproductionmentioning
confidence: 99%
“…The mechanism of the sensory information addition action, especially the subpatellar strip, has not yet been fully elucidated. The main hypothesis, found in studies, suggests the increase of afferents by constant cutaneous stimulation, greater stimulation to the superficial skin receptors and local receptors, with consequent improvement of the articular proprioceptive response (12)(13)(14)(15)(16)22) . Older fallers present reduced mobility and are more likely to decrease muscle strength caused by aging and inactivity, with consequent impact on walking and stabilization of the ankle and hip (36).…”
Section: Discussionmentioning
confidence: 99%
“…The additional sensory information is also the great importance for healthy individuals, as long as it provides useful information for carrying out the proposed task (8)(9)(10) . The first studies using the addition of sensory information proved their efficacy in healthy individuals, but it is of greater relevance in subjects with proprioceptive deficit (9,11,15,16) . Therefore, the geriatric population can benefit from the effect of additional sensory information, which is a low-cost tool which may help maintain postural balance and reduce the risk of falls (13) .…”
Section: Introductionmentioning
confidence: 99%